Improving Early Childhood Language Development through “Kiki Miu-Miu” YouTube Videos - Jasiah; Umul Khasanah; Wina Asry; Nur Latifah; Zulham (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2023)
This article aims to examine the importance of language development in early childhood, specifically focusing on the YouTube video